Kingdom hearts II : the novel, Vol. 2 - Kanemaki, Tomoko, 1975- (Yen On, 2017)
Sora, Donald, and Goofy are on a mission to locate Riku and Mickey. But Sora is faced with the difficult task of uncovering the truth about Organization XIII's intentions.